Risk Factors of Very Severe Pneumonia Incidence in Children - Retno Asih Setyoningrum; Hedi Mustiko (Jurnal Respirologi Indonesia, 2020)
Background: Childhood pneumonia is a significant cause of mortality and morbidity in developing countries. About 7-13% of childhood pneumonia present with very severe pneumonia with a high risk of mortality. Identification of risk factors is necessary for early intervention and better management. Methods: Analytic observational study with a cross-sectional approach was conducted with subjects of pneumonia patients aged 2-59 months admitted in Respirology Ward and PICU Department of Pediatrics Dr. Soetomo Surabaya from January 2017 to December 2018. Results: A total of 253 were roled in this study. Group with very severe pneumonia are 140 patients and 113 patients with severe pneumonia. Independent risk factors were analysed by chi-square test and Continuity Correction. Independent risk factors that intluence the incidence of very severe pneumonia in infants and children are patient's age (PR=1.365;P=0.009;95% confidence interval (CI)=1.089-1.712), low birth weight (PR=1.380;P=0.010;95% CI=1.115-1,708), prematurity (PR=1,412;P=0.007;95% CI=1,141-1,747), exclusive breastfeeding (PR=1,434;P=0.007;95% CI=1,093-1,880), nutritional status (PR=2,412;P